Public Health System in Brazil nowadays: challenges for its operation and funding - Alethele de Oliveira Santos; Sandra Mara Campos Alves (Oswaldo Cruz Foundation, Health Law Program, 2016)
This paper has the aim to revisit the theme of the brazilian public health system from the perspective of its operation and funding of its actions and services, analyzing some of the main obstacles to its effectiveness. Endowed with its own logic of organization, planning and funding of its actions and services, the Brazilian Unified Health System (SUS) finds barriers to its sustainability when it comes to funding and the judicialization of health. Historical under-funding worsened by the economic and political crisis the country currently faces plus the increase in casuistic judicial decisions that prioritize the individual logic over the collective right have produced serious shocks in the system. These are just some of the challenges to an effective public health system. This is why the work of public bodies must be responsible and always take into consideration the collective dimension of the right to health under penalty of causing the collapse of the public health system altogether